Kajian Kebutuhan Aplikasi Pembelajaran Berbasis Android Untuk Meningkatkan Kemampuan Pemecahan Masalah Dan Minat Belajar Matematika Peserta Didik - Rizky, Muhammad Rafi Fajar; Marhaeni, Nafida Hetty; Budiningsih, Veronica Anita (Jurnal Sains dan Teknologi (JSIT), 2022)
In learning mathematics, it is required to have problem solving skills and interest in learning mathematics because it can help students achieve better learning achievements. One of the reasons for the low problem solving ability and interest in learning mathematics among students is that the teaching materials still use books. Therefore, the purpose of this study was to examine the need for an Android-based learning application to improve problem solving skills and students' interest in learning mathematics. The research subjects were students of class 10 MIPA 2 SMA Negeri 1 Pengasih. Data collection techniques used interviews, observations, and distributing questionnaires as well as the results of students' daily tests. This study has several results. First, the learning application is considered interesting for students. Second, the teaching materials used today are considered insufficient to improve problem solving skills and students' interest in learning mathematics. Third, 89% of students are interested if the material is packaged into a learning application. From this study it was concluded that learning applications need to be applied to improve problem solving abilities and students' interest in learning mathematics.